2000
DOI: 10.1002/1099-0984(200007/08)14:4<325::aid-per380>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional models of core affect: a quantitative comparison by means of structural equation modeling

Abstract: The present article compares dimensional models of affect with each other. The article focuses on the pleasure–arousal model, the energetic and tense arousal model, and a three‐dimensional model with separate pleasure–displeasure, awake–tiredness, and tension–relaxation dimensions. The results show that the three‐dimensional model cannot be reduced to a two‐dimensional model. Problems of the two‐dimensional models' reductionism are discussed. We conclude that a three‐dimensional description of affect is necess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
181
1
6

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 251 publications
(195 citation statements)
references
References 38 publications
7
181
1
6
Order By: Relevance
“…Under this formulation, high positive affect involves the experience of elation, enthusiasm, and excitement, and high negative affect involves feelings of distress, fear, hostility, and nervousness (Watson, Wiese, Vaidya & Tellegen, 1999). The decision to adopt Watson and colleagues' conceptualization of affectivity was primarily guided by the literature that was included in the current meta-analysis; a preponderance of the studies included in the current paper employed Watson and Clark's formulation of affect, which is consistent with the prevalence of this approach in psychology and management science (Schimmack & Grob, 2000). Moreover, our conceptualization of affect is consistent with evidence that has supported the dispositional nature of positive and negative affect, including evidence of its heritability and stability over time (Watson, 2004), supporting the use of positive and negative affectivity as traits in the current study.…”
Section: Leader Trait Affectmentioning
confidence: 82%
“…Under this formulation, high positive affect involves the experience of elation, enthusiasm, and excitement, and high negative affect involves feelings of distress, fear, hostility, and nervousness (Watson, Wiese, Vaidya & Tellegen, 1999). The decision to adopt Watson and colleagues' conceptualization of affectivity was primarily guided by the literature that was included in the current meta-analysis; a preponderance of the studies included in the current paper employed Watson and Clark's formulation of affect, which is consistent with the prevalence of this approach in psychology and management science (Schimmack & Grob, 2000). Moreover, our conceptualization of affect is consistent with evidence that has supported the dispositional nature of positive and negative affect, including evidence of its heritability and stability over time (Watson, 2004), supporting the use of positive and negative affectivity as traits in the current study.…”
Section: Leader Trait Affectmentioning
confidence: 82%
“…Lower life satisfaction has been linked to eveningness (Díaz-Morales et al 2013) and similar results have been observed for affect. Among various conceptualizations, a three-dimensional model of mood seems to cover the widest denotation of core affective experience (Schimmack & Grob 2000). In the framework developed by Matthews et al (1990) three dimensions of affect have been distinguished: energetic arousal (energetic-tired), tense arousal (nervous-relaxed), and hedonic tone (pleasant-unpleasant).…”
Section: Introductionmentioning
confidence: 99%
“…With self-reported data, researchers found that emotions can be plotted in a two-dimensional space, with one axis representing the hedonic value (positive versus negative or pleasant versus unpleasant) and the other axis representing the level of activation 1 (high versus low). There is considerable agreement on the first factor (e.g., Green & Salovey, 1999;Russell & Feldman Barrett, 1999), but the existence of an independent general activation dimension is more controversial (Schimmack & Grob, 2000;Watson, Wiese, Vaidya, & Tellegen, 1999). The extraction of this activation dimension varies across samples.…”
mentioning
confidence: 99%